Hydrometeorological dataset (2018–2023) from the largest Portuguese reservoir: 2 weather stations located at the shore and centre of the reservoir - Rodrigues, Gonçalo (2024)
The databases provided for two meteorological stations installed in the Alqueva reservoir (the largest artificial lake in Europe), one located on a floating platform and the other on the shore (approximately 1 km away in a straight line), cover a period of 6 years, from 2018 to 2023. The data available are, the hourly accumulated precipitation as well as the hourly averages of surface water temperature (0.25 m of depth), soil temperature, and meteorological parameters (wind intensity and direction, relative humidity, upward/downward solar radiation, air temperature, and relative humidity). Additionally, daily maximum and minimum values of the air temperature and relative humidity are provided, together with the time at which they were recorded. These data can potentially be used for various purposes, including hydrometeorological analysis, monitoring and assessing local environmental conditions, analysing local meteorological patterns, integrating or validating results from high-resolution numerical model simulations, or gaining a better understanding of changes in water quality or microalgae blooms in large reservoirs. The percentage of failures/gaps per parameter for each hour and day is provided to give users the flexibility to choose their own requirements regarding the maximum acceptable limit.